A note on the parabolic identification problem with involution and Dirichlet condition - Ashyralyev, A.; Erdogan, A.S.; Sarsenbi, A. (KSU Publ., 2020)
A space source of identification problem for parabolic equation with involution and Dirichlet condition is studied. The well-posedness theorem on the differential equation of the source identification parabolic problem is established. The stable difference scheme for the approximate solution of this problem is presented. Furthermore, stability estimates for the difference scheme of the source identification parabolic problem are presented. Numerical results are given.
Дирихле шартымен және инволюциясымен сәкестендірілген параболалық теңдеу туралы ескерту
Замечание о параболической проблеме идентификации с инволюцией и условием Дирихле
Keywords: well-posedness; elliptic equations; positivity; coercive stability; source identification; exact estimates; boundary value problem